Overcoming Heretical Sects Through Fatwa of the Ulama Consultative Council and Qanun - Chifa Azyana Adly Meknesya; Ansari Yamamah (AT-TAFAHUM: Journal of Law, 2018)
One of the social phenomena in the midst of religious life in Aceh is the emergence and development of deviant sect, This phenomenon is considered alarming because remembering Aceh is a region that is trying to implement Islamic law in every part of its life and is known as an area that has a strong Islamic culture in Acehnese society from ancient times, seeing this incident, the stakeholders in Aceh took steps to overcome it, one of them was by issuing qanun and fatwa, the efforts to deal with the two legal products were preventive, repressive, and curative. The purpose of this research is to find out the role of qanun set by the government in overcoming the criminal offenses of cults so that they can become social controllers on the issue of cults that developed in Aceh Province, Knowing the role of the fatwa stipulated by the Ulama Consultative Assembly in overcoming the crime of heretical sects so that they can become a social controller on the issue of cults which developed in Aceh Province. To find out the process carried out by the government in acting or punishing deviant sect. The method used in this study is qualitative, this study at the Islamic Syariat office of the city of Banda Aceh, the time of this research was carried out from march to December 2018.The results of this study state that efforts that synergize between qanun and fatwa in tackling cases of cults still need to be improved, so as to anticipate the growth and spread of cults, the forms of mitigation carried out are preventive, repressive and curative, but even so the handling process is in practice not yet maximal, still impressed incidental and running as a minimum, so that the potential for the same case to occur again.